2001
DOI: 10.1073/pnas.131057498
|View full text |Cite
|
Sign up to set email alerts
|

A novel application of gene arrays: Escherichia coli array provides insight into the biology of the obligate endosymbiont of tsetse flies

Abstract: Symbiotic associations with microorganisms are pivotal in many insects. Yet, the functional roles of obligate symbionts have been difficult to study because it has not been possible to cultivate these organisms in vitro. The medically important tsetse fly (Diptera: Glossinidae) relies on its obligate endosymbiont, Wigglesworthia glossinidia, a member of the Enterobacteriaceae, closely related to Escherichia coli, for fertility and possibly nutrition. We show here that the intracellular Wigglesworthia has a red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…In a previous study, where we hybridized DNA of W. pallidipes (a relative of W. brevipalpis studied here) to heterologous Escherichia coli gene arrays, we detected 457 orthologs, 197 of which were present in the genome of W. brevipalpis 8 . The additional homologous genes detected on the E. coli array may have been an artifact resulting from the extremely high AT content of the W. glossinidia genome.…”
Section: Lettermentioning
confidence: 84%
See 1 more Smart Citation
“…In a previous study, where we hybridized DNA of W. pallidipes (a relative of W. brevipalpis studied here) to heterologous Escherichia coli gene arrays, we detected 457 orthologs, 197 of which were present in the genome of W. brevipalpis 8 . The additional homologous genes detected on the E. coli array may have been an artifact resulting from the extremely high AT content of the W. glossinidia genome.…”
Section: Lettermentioning
confidence: 84%
“…The genome size of W. glossinidia has been estimated as 740-770 kilobases 8 (kb), and that of Buchnera sp., the obligate symbiont of the pea aphid (Homoptera:Aphidoidea), as 640,681 bp 9,10 . Both genomes approach the size of the smallest genome reported thus far, that of Mycoplasma genitalium (580 kb) 11 .…”
mentioning
confidence: 99%
“…brucei brucei since this insect form grows in a medium that lacks carbohydrate other than what is present in the serum. Production of ammonia by trypanosomes was of further interest since it has been suggested that the tsetse fly (Diptera: Glossinidae) relies on an endosymbiotic bacterium for its fertility and nutrition (Akman & Aksoy, 2001). Based upon Escherichia coli gene array analysis, one of the endosymbionts (Wigglesworthia) was suggested to utilize ammonia in the absence of trypanosomes.…”
mentioning
confidence: 99%
“…Sequencing of W. glossinidia genome revealed the presence of several cofactor biosynthetic pathways, including over 60 genes involved in the synthesis of vitamins and nutrients that are necesssay for fly fertility (Akman et al, 2002). The expression profile of these genetic pathways has also been confirmed using microarrays (Akman et al, 2001a). Moreover, a clear reduction in the number of bacterial genes related to the typical free-living state has been reported.…”
Section: Camponotus Floridanus Camponotus Pennsylvanicusmentioning
confidence: 86%
“…Among the most important genes lost is the DNA replication initiation protein, DnaA, which may reflect the dependency of W. glossinidia on host genome functions and may be one mechanism by which the host controls symbiont numbers (Akman et al, 2002). Studies of the gene expression in Wigglesworthia have been conducted using E. coli gene arrays, which have suggested that Wigglesworthia could be a facultative anaerobic organism that utilises ammonia as its major source of nitrogen (Akman et al, 2001a). The secondary symbiont of the tsetse fly is the S-symbiont Sodalis glossinidius (Akman et al, 2001b).…”
Section: Camponotus Floridanus Camponotus Pennsylvanicusmentioning
confidence: 99%